A study on the acoustic system in multi-purpose auditorium / Mohd Khairul Fahmie Ashar - Fahmie Ashar, Mohd Khairul (Faculty of Architecture, Planning and Surveying, 2014)
Multipurpose auditorium is an auditorium build to suit with numeral occasions. For such functions, the needs of acoustic in enclosed area are important as it will determine whether the auditorium is eligible to perform such occasions. The differences of requirement for each occasion must be considered in order to achieve a high quality of hearing especially to audience. A good acoustic system will influence the performance, and also creating a high quality and standard to the occasion itself.